Challenges of the Developing World - Handelman, Howard (Lanham Rowman & Littlefield, 2017)
Previously published by Pearson Education, Inc. under the title The challenge of third world development.
Include Tables, Glossary ad Index.
Keywords: Developing countries -- Politics and government -- Economic development